PENGARUH DAYA TARIK FASILITAS, CITRA MEREK, DAN PERSEPSI HARGA, TERHADAP MINAT KEMBALI BERKUNJUNG KE HOTEL: ASTON MAKASSAR - Hariyanto R Djatola Djampagau; Nur Hilal (Eqien - Jurnal Ekonomi dan Bisnis, 2025)
This study aims to analyze the influence of facility attractiveness, brand image, and price perception on guests' intention to revisit Aston Makassar Hotel. These three variables are considered key factors that impact guests' likelihood of returning. The research was conducted through a survey of hotel guests, using questionnaires and interviews as data collection methods. Since the sample size was unknown, the Lemeshow formula was applied to determine a sample of 100 respondents. The study employed a non-probability sampling technique, specifically using accidental sampling and purposive sampling methods. Data were analyzed using multiple regression analysis to assess the significance of each variable's influence. The results indicate that facility attractiveness, brand image, and price perception significantly affect guests' intention to return. Attractive and high-quality facilities enhance guest satisfaction, while a strong brand image builds trust and loyalty, encouraging repeat visits. Additionally, price perception that aligns with service quality and facilities is a crucial factor in guests' decision-making. The implications of this study suggest that the hotel should optimize its facilities, strengthen its brand image, and establish competitive pricing strategies to enhance guests' intention to revisit.